Quadcopter based Automatic Spattering of Pesticides and Fertilizers - K. N. Baluprithviraj; P. Naveena; R. Palanisamy (Journal of Electronic Design Engineering, 2016)
Agriculture plays a major role in Indian Economy. The crop yield depends upon the pesticides and fertilizers applied in the fields. But the manual handling of these things leads to health hazards. The World Health Organization (WHO) estimated that over 3 million cases of pesticides poison each year, which is majority in developing countries like India. This paper aims to overcome the problem by automating the spray of pesticides and fertilizers in the fields. The system is constituted by an aerial sprayer which consists of a Quadcopter and spraying mechanism. The Quadcopter is controlled by the Radio Frequency signals and the spraying of pesticides is achieved with less manual labour without any health issues. This paper is to mainly overcome the ill-effects of pesticides on human beings and also to cover larger areas with short span of time.